The Crackers of Modified Cassava Flour (MOCAF) and Cowpea Flour: Chemical and Sensory Properties - Artina, Zahra J; Ayu, Dewi F; Rahmayuni, Rahmayuni (AGRITEKNO: Jurnal Teknologi Pertanian, 2023)
Crackers are a type of snack that people of all ages like. They come in many different shapes and flavors and are sold in a lot of places. This research aimed to determine the best formulation of crackers using modified cassava flour (MOCAF) and cowpea flour based on their chemical and sensory properties. A completely randomized experimental design with five treatments and three replications was performed. The treatments were MKT0 (100 g MOCAF), MKT1 (90 g MOCAF:10 g cowpea flour), MKT2 (80 g MOCAF:20 g cowpea flour), MKT3 (70 g MOCAF:30 g cowpea flour), and MKT4 (60 g MOCAF:40 g cowpea flour). Chemical content (moisture, ash, protein, and fat), color analysis with a chromameter, and sensory assessment were observed. Based on the results obtained, 70 g MOCAF:30 g cowpea flour was the best treatment, which had 4.70% moisture, 1.76% ash, 8.34% protein, 17.79% fat, 77.59 L*, 6.46 a*, and 26.57 b* values in the color analysis. The crackers had a cream-brown color, a cowpea aroma, a cowpea taste, and a crunchy texture. The panelists also favored the overall hedonic assessment of the MKT3 crackers with a score of 1.60 (like).